Shariah Governance Practices at Islamic Banks in Bahrain From Islamic Bankers’ Perspective - Hidayat, Sutan Emir; Al-Khalifa, Ali Khaled (UNIVERSITAS ISLAM NEGERI SYARIF HIDAYATULLAH JAKARTA, 2018)
This study aims to evaluate the Islamic banks' commitment towards Sharia Governance in Bahrain. This study utilizes both quantitative and qualitative research methods. The survey results reveal that Islamic banks in Bahrain practice 7 out of 9 questions in the questionnaire, which are related to Sharia governance aspects as per the Accounting and Auditing Organization for Islamic Financial Institutions (AAOIFI)'s governance standards. The interview results also reveal that the Islamic banks are practicing most aspects of Sharia governance. The results of this paper can be an input for the regulator and the banks' management to make decisions to improve Sharia governance practice among Islamic banks in Bahrain.DOI: 10.15408/aiq.v10i1.5991